Effects of Environment and Sowing Time on Growth and Yield of Upland Cotton (Gossypium hirsutum L.) Cultivars in Sicily (Italy) - Tuttolomondo, Teresa (Plants (Basel), 2020)
Cotton is one of the most important industrial crops in the world. Though widely cultivated in Sicily (Italy) in the past, cotton growth on the island has disappeared today due to a complex variety of agronomic, economic and socio-political reasons. In recent years, increased interest in natural fibers worldwide has led to a revival in cotton plants in the Mediterranean area. The aim of this paper was to assess the response of Gossypium hirsutum L. cultivars to different environments and sowing times. Elsa and Juncal were selected from the most promising cotton cultivars regarding earliness and productivity. Plants were tested with three sowing times and in two Sicilian environments. Cotton yield and yield components were significantly affected by experimental station, sowing time and cultivar. Lint yield of cultivars was 1.60 t ha(−1) on average, and the highest value of 1.99 t ha(−1) was obtained from an early sowing time. The three indices of agronomic earliness varied significantly based on treatments. In conclusion, the evaluation of response genotype-by-environment under different sowing times could represent a strategy to obtain optimal cotton seed and lint yields, although other general aspects, such as labor costs, land availability and capital resources, should be also considered when evaluating the reintroduction of the species in Sicily.